Cyber physical systems : concepts and applications - Baliyan, Anupam, 1976-; Kaswan, Kuldeep Singh; Kumar, Naresh, 1983-; Upreti, Kamal; Kannan, Ramani (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Cyber Physical System (CPS) is an integration of computation, networking, and physical processes: the combination of several systems ofdifferent nature whose main purpose is tocontrol a physical process and, through feedback, adapt itself to new conditions, in real time.Cyber Physical System: Concepts and Applications includes an in-depth coverage of the latestmodels and theories that unify perspectives. This book is primarily aimed at advanced undergraduates, graduates of computer science. Engineers will also find this book useful"--
OCLC-licensed vendor bibliographic record.
Keywords: Cooperating objects (Computer systems); COMPUTERS / Computer Architecture